The Formation of Language as a System (Journal of Pedagogical Inventions and Practices, 2022)
In world linguistics, there are many ancient views on the relationship between language units, in particular, paradigmatic and syntagmatic, their features, different views, information about the contradictions between language units. In the first quarter of the last century, language gave rise to the view on the same basis, just as all phenomena in nature and society have their own system.